Forks Over Knives - Fulkerson, Lee; Aucoin, Joey; Barnard, Neal D., 1953-; Baur, Gene (New York, NY : Virgil Films, 2011)
Examines the possibility of eliminating diseases like heart disease and diabetes through a plant-based diet.
Originally released as a motion picture in 2011.
Features: new & deleted scenes, discussions with the filmmakers, vegan recipes, Dr. Neal Barnard explains diabetes video.
New DVD 2023 Summer.
Featuring Joey Aucoin, Neal Barnard, Gene Baur.
MPAA rating: PG.
DVD.
Keywords: Nutritionally induced diseases; Vegetarianism; Veganism; Documentary films; Nonfiction films; Feature films